The military history of World War II - Pitt, Barrie (New York Military Press, 1986)
Includes chronology of the war with illustrations of bombers, battleships, tanks, rifles, pistols and machine-guns used on each front.
Prelude to conflict -- Blitz in the West -- Britain alone -- Italy falters -- Hitler strikes South -- Enter Rommel -- Barbarossa -- The War against Japan -- The onslaught continues -- From Moscow to the Crimea -- Turning point in the desert -- Stalingrad to Kursk -- Victory in the desert -- The Convoy battles -- Hitting back against the Japanese -- The Italian armistice -- To the Gustav Line -- Approaches to the Philippines -- War over the Reich -- The invasion of France -- Destruction of the Army Group Centre -- The Seine to Arnhem -- The Empire's last throw -- Victory in Italy -- The end in Europe -- Victory over Japan.
Includes index.
Keywords: World War, 1939-1945.